On the problem of forming a theoretical and methodological platform of environmental education - Baluta Галина (Actual Problems of Mind, 2022)
Іn the XXI century, more attention is drawn to the development of ecological thinking. Instead of explicating treatment of nature, a human being should take care of it. Such a caring attitude should become an educational universal, so it is to be transmitted as value. Ecological culture is analyzed as ethics of conservation аnd hermeneutic practice. However, the ecological-discursive paradigm is still problematic in education. A serious drawback of education is the fragmentation of knowledge, the lack of a methodological platform that provides a picture of the unity of the world, the "family kinship" of its phenomena. Reproduction of the general picture is a possible way of introducing ethical "understanding" discourse into the cognitive horizon. Therefore, the objective of the paper is to analyze it as a complex approach in philosophy of education. The paper considers environmental anthropology as the methodological basis of the ecological-discursive paradigm, and also a theoretician-methodological platform of environmental education: а) the concept of the value of life and its continuation in all manifestations and forms (A. Schweitzer), b) holistic worldview, с) communicative ethics, integral methodological pluralism as different ways of interpreting the essence (К. Wilber) d) new models of cognition. The paper emphasizes that ecological thinking cannot be developed without changing an epistemological model. Thus, instead of facts and competences, the person’s cognition should be based on values. The paper highlights the idea of diagnostic cognition, which is based on values. Therefore, the metaphysical picture of the world has a significant theoretical and methodological potential, which unfolds in the cognitive and ethical horizon and is a practice of educational reflection that integrates different types of rationality, interprets the process of modernization in education as the rehabilitation of ontological values displaced by the instrumental values of technological progress.